On the combined role of the astrophysical force limit and Avogadro number in final unification - UV, Satya Seshavatharam; S, Lakshminarayana (International Journal of Advanced Astronomy, 2014)
Magnitude of the unified force can be assumed to be equal to the classical or astrophysical force limit . Strength of any interaction can be defined as the ratio of the operating force magnitude and the magnitude of . Let the gravitational interaction taking place at black holes be called as â€˜Schwarzschild interactionâ€™. If strength of Schwarzschild interaction is unity, then weak interaction strength seems to be times less than the Schwarzschild interaction and strong interaction strength seems to be Â times less than the Schwarzschild interaction. Based on these concepts and considering the Avogadro number as an absolute and discrete number, basics of final unification can be understood.